NATIONAL DESIGN AS A COMPLEX SYSTEM: RESEARCH, EVOLUTION, LEARNING - Ковальов, Юрій Миколайович; Дяченко, Алла Володимирівна (Art and Design, 2024)
The aim of the work is to present the properties of national design as a complex system, relevant research methods, characteristics, scenarios, examples and predictions of evolution, the results of research into the educational process. The work methodology is based on the concepts of a complex open system, which compares the structure and interactions of the components of national design, and a systemic approach, includes methods of selection and ranking of sources and artifacts, as well as hermeneutic, comparative and systemic analysis, models of the evolutionary process based on previously obtained results and adapt to the needs of research, reconstruction, forecasting and statistical processing of student survey data. The correctness of the comparison of the structure of components and ties of national design with complex open systems is substantiated, which makes it possible to use models and scenarios of self-organization of such systems for researching the evolution of national design and optimizing the educational process. Adapted to the needs of research, models of the system of human interactions with the environment and its evolution during the existence of a modern type of man are presented, correlations between the expressive means of national styles in different eras and the evolution of the system of interactions are established. Sources and artifacts from different eras, selected and analyzed using special methods, were used for verification. Examples of the analysis of the evolution of national styles and the identification of relatively constant and variable characteristics are given. The results of the processing of the students’ survey are presented in order to determine the directions for the optimization of the educational process. The scientific novelty consists in the correct statement of the problem of the study of the evolution of national styles based on the general wave axiomatic model C – space and scenarios of self-organization of complex systems, as well as individual models of evolution adapted to the needs of the study; correct, based on special methods, selection of sources and artifacts, results of hermeneutic analysis (correlation of stages of evolution and means of expression); characteristics of the process of development of national styles; the results of measuring indicators and optimizing the educational process. Examples of the selection and ranking of sources, hermeneutic analysis, modeling and determination of the characteristics of national styles, measurement and optimization of indicators of the educational process are provided, which illustrate the practical use of the presented scientific apparatus and the possibilities of its application for solving various problems of the study of national styles.